Nilai-Nilai Hak Asasi Manusia Dalam Penanganan ODGJ di Kota Tasikmalaya Berdasarkan Undang-Undang Republik Indonesia Nomor 19 Tahun 2011 - Muhamad Yusron; Wiwi Widiastuti; Fitriyani Yuliawati (Epistemik Press, 2022)
In this journal, the author will discuss the odgj issues in Tasikmalaya City and how stakeholders in Tasikmalaya City perform respect, protection and fulfillment of ODGJ rights. This research shows ODGJ from various perspectives including the perspective of the community with the study of Laws and Regulations, namely Law No. 19 of 2011 concerning the Convention on the Rights Person with Disabilities / CRPD, where in the Law focuses on human rights values that must be applied in handling ODGJ, such as recognition and elimination of discrimination and stigma against ODGJ. Theories used in this study are the theory of Democracy and Human Rights and the concept of Public Policy. This journal will focus on discussing the presence of the state in handling ODGJ, in this case stakeholders in Tasikmalaya City who have a relationship regarding ODGJ issues. The method used in this study is Descriptive Qualitative with Interactive Analysis techniques. Where the results of the discussion of this study are the implementation of respect for the Protection and Fulfillment of ODGJ Rights which cannot be done optimally due to various factors. Communities/families with ODGJ members and stakeholders are key in this research.